舌に発生した平滑筋腫の1例 - 浅野, 真衣; 高田, 直樹; 渋谷, 恭之; 古森, 孝英; 木本, 明; 竹内, 佑香 (日本口腔外科学会雑誌, 2013)
Leiomyoma is a benign tumor of smooth muscle origin, and usually arises in the uterus, alimentary tract, and skin. Since the first report by Blanc in 1884, most reported leiomyomas have been angioleiomyomas. In the present report, we describe a rare type of leiomyoma arising in the tongue of a 25-year-old woman. The tumor was an 18 × 7 mm, well-demarcated, and slow growing mass located in the right margin of the tongue. The entire lesion was excised, and the pathological diagnosis was solid leiomyoma. The patient has been followed up for 1 year 2 months after surgery, without any evidence of recurrence.